2001
DOI: 10.1002/1097-4636(20011215)57:4<567::aid-jbm1203>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory mechanism of gap junctional intercellular communication induced by polyethylene and the restorative effects by surface modification with various proteins

Abstract: Gap junctional intercellular communication (GJIC) is a function that plays an important role in maintaining cell and tissue homeostasis and in regulating cell growth, development, and differentiation. Change in this function of V79 fibroblasts cultured on polyethylene films modified with albumin or collagen was estimated using fluorescence redistribution after photobleaching (FRAP) analysis. The GJIC function of V79 cells on nontreated polyethylene was strongly inhibited in comparison with those on a glass cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…and intercellular communication, compared with laminin-rich Matrigel (22). Numerous other studies also have shown that the ECM can directly and indirectly alter gap junctional communication in various cell types (5,24,25). These results, in combination with our own, strongly suggest that the ECM can influence both the expression and function of gap junctions.…”
Section: Discussionsupporting
confidence: 86%
“…and intercellular communication, compared with laminin-rich Matrigel (22). Numerous other studies also have shown that the ECM can directly and indirectly alter gap junctional communication in various cell types (5,24,25). These results, in combination with our own, strongly suggest that the ECM can influence both the expression and function of gap junctions.…”
Section: Discussionsupporting
confidence: 86%
“…NHOst cultured on SAM‐covered coverslips were subjected to fluorescence recovery after photobleaching (FRAP) analysis to evaluate the effect of these surfaces on the GJIC. FRAP analysis was carried out according to the procedure of Wade et al26 with some modifications 20. Briefly, NHOst were plated and incubated for 1 day on the SAM‐covered coverslips.…”
Section: Methodsmentioning
confidence: 99%
“…It suggests that inhibitory action of PS microspheres is not due to the change in the connexin status. From our previous study, 24) however, the expression of connexin 43 in fibroblasts cultured on a PE film was apparently different from that on a normal culture dish, suggesting that an interaction between the cell and PE surface resulted in irregular intracellular signal transduction, followed by abnormal expression of connexin. It was reported that the phosphorylated state of connexin 43 was important for its accurate assembly and distribution inside the cell.…”
Section: Discussionmentioning
confidence: 82%